2022
DOI: 10.1002/joc.7819
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Trans‐Volcanic Axis on meridional propagation of summer precipitation in western Mexico

Abstract: The Trans-Volcanic Axis (TVA)-comprising ridges and terrain elevations above 1,900 m-strongly affects meridional propagation of summer precipitation in western Mexico. This barrier modifies atmospheric moisture content and changes the annual precipitation cycle configuration, which distinguishes it from the precipitation cycle on both sides of the TVA. Using upper-air observations and rainfall records, this study demonstrates that the TVA is the region where the North American monsoon (NAM) and the mid-summer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Remarkably, a bimodal distribution is observed only in the NW subregion (active vs. inactive season), which has been related to the influence of the North American Monsoon (Boos & Pascale, 2021; Ramos‐Pérez et al, 2022). The highest thunderstorm activity in FV has been associated with the role of complex terrain features in generating deep convection (Brito‐Castillo et al, 2022; León‐Cruz et al, 2021). The GM and YP seasonal patterns are associated with the previously mentioned tropical activity (i.e., easterly waves and tropical cyclones) over the Caribbean Sea.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Remarkably, a bimodal distribution is observed only in the NW subregion (active vs. inactive season), which has been related to the influence of the North American Monsoon (Boos & Pascale, 2021; Ramos‐Pérez et al, 2022). The highest thunderstorm activity in FV has been associated with the role of complex terrain features in generating deep convection (Brito‐Castillo et al, 2022; León‐Cruz et al, 2021). The GM and YP seasonal patterns are associated with the previously mentioned tropical activity (i.e., easterly waves and tropical cyclones) over the Caribbean Sea.…”
Section: Resultsmentioning
confidence: 99%
“…For this portion of the country, intermediate-low shear and low-CAPE environments are typical for the formation of thunderstorms and hailstorms. Previous investigations have suggested the critical role of orography as a primordial mechanism for lifting and trigged convection (Brito-Castillo et al, 2022;Le on-Cruz et al, 2021). Further investigations are required to create a proper severe weather index for regions with such characteristics.…”
Section: Composite Parameters and Covariatesmentioning
confidence: 99%
See 1 more Smart Citation
“…Hourly observations of air temperature (AT, °C), relative humidity (RH, %), atmospheric pressure (AP, hPa), wind (W, m/s) and zonal (U, east-west m/s) and meridional wind (V, north-south, m/s) components were covered during the period from 1 January In winter, several midlatitude systems predominate, such as cold fronts, air masses, and jet streams [14,19,30], while in summer, rainfall is primarily controlled by the North American monsoon (NAM) system [16,[32][33][34][35][36] and numerous transient disturbances, such as mesoscale convective systems, tropical cyclones, easterly waves, inverted troughs, the Madden Julian oscillations, and midlatitude troughs. Wang and Fiedler [37] noted that ENSO is a coupled phenomenon in the ocean-atmosphere system that causes climate variability in the GoC.…”
Section: Datamentioning
confidence: 99%
“…Additionally, Farfán et al [21] identified a persistent deep convection region along and off the coast of Nayarit, while another study [23] showed that summer rainfall behaves in a contrasting way along coastal Nayarit to that observed on the Mexican Altiplano. It is important to note that this region is positioned in the transition zone where the annual precipitation cycle changes from the double precipitation peak with the midsummer drought to the south, to a single rainfall peak characteristic of the monsoon in the north [24]. All these features are important to understand seasonal and interannual precipitation variabilities in Western Mexico.…”
Section: Introductionmentioning
confidence: 99%